Interaction of Warfarin with Human Serum Albumin and Effect of Ferulic Acid on the Binding. (3rd April 2014) - Li, Qiang; Yang, Wen-yue; Qu, Ling-ling; Qi, Huan-Yang; Huang, Yun; Zhang, Zheng
Abstract : Angelica sinensis (Oliv.) Diels combined treatment with warfarin would increase the risk of bleeding. Ferulic acid is an abundant hydroxycinnamic acid in A. sinensis and warfarin is the most widely used oral anticoagulant. The studies on supermolecular interaction of warfarin with human serum albumin (HSA) and the influence of ferulic acid on the binding would contribute to the understanding of the metabolic processes of warfarin and the effect of ferulic acid. We focus on investigating the effect of warfarin on fluorescence spectrum of human serum albumin (HSA), fluorescence quenching mechanism, binding constant, Hill coefficient, binding mode, and the effect of different ferulic acid concentrations on the binding. Warfarin quenched the intrinsic fluorescence of HSA mainly by static quenching. Accession of ferulic acid reduced the binding of HSA-warfarin. By decreasing binding constant and the Hill coefficient of warfarin with HSA, ferulic acid could improve the plasma concentration of free warfarin, which would increase the risk of bleeding. Warfarin's free concentration increased at least 50% under the condition of simulated human body. The results indicated that A. sinensis combined treatment with warfarin would increase the risk of bleeding. And the results provide an important theoretical support for warfarin used as oral anticoagulant.